2021
DOI: 10.1101/2021.02.15.21251423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-quantity lipid-based nutrient supplements for children age 6-24 months: a systematic review and individual participant data meta-analysis of effects on developmental outcomes and effect modifiers

Abstract: Background: Positive effects of SQ-LNS on developmental outcomes have been found in some trials, but not others. Objectives: Our objectives were to generate pooled estimates of the effect of SQ-LNS, compared to control groups that received no intervention or an intervention without any nutritional supplement, on developmental outcomes and to identify study-level and individual-level modifiers of these effects. Methods: We conducted a two-stage meta-analysis of individual participant data from 14 intervention v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 60 publications
(81 reference statements)
4
23
0
Order By: Relevance
“…However, even when the magnitude of effect differed between subgroups, the magnitude of the modifying effects was generally small and we observed positive effects of SQ-LNSs within all subgroups, indicating the potential of SQ-LNSs to provide benefits across a range of individual, population, and study design characteristics. This was also the case for the growth ( 19 ) and development ( 20 ) domains of this meta-analysis.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, even when the magnitude of effect differed between subgroups, the magnitude of the modifying effects was generally small and we observed positive effects of SQ-LNSs within all subgroups, indicating the potential of SQ-LNSs to provide benefits across a range of individual, population, and study design characteristics. This was also the case for the growth ( 19 ) and development ( 20 ) domains of this meta-analysis.…”
Section: Discussionsupporting
confidence: 68%
“…Although the overall effects on anemia and moderate-to-severe anemia were more modest (16% and 28% reductions, respectively), this likely reflects the presence of anemias in these populations that are not nutrition responsive (e.g., genetic Hb disorders and infection and inflammation). Alternative interventions, including micronutrient supplementation, MNP, and food fortification, are also effective in reducing anemia and the prevalence of iron deficiency ( 8 , 54 ); however, SQ-LNS provides the added benefits of reducing mortality ( 78 ), stunting, and wasting ( 19 ) and improving developmental outcomes ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this article, our objectives were to generate pooled estimates of the effect of SQ-LNSs on each growth outcome and identify study-level and individual-level modifiers of the effect of SQ-LNSs on these outcomes. Two companion articles report results for other outcome domains: anemia and micronutrient status ( 17 ) and development ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews have demonstrated a 16%–21% reduction in anemia ( 25 , 33 ), a 56% reduction in iron deficiency ( 33 ), and a 64% reduction in iron deficiency anemia ( 33 ) when SQ-LNSs are provided, similar to the efficacy of MNPs. SQ-LNSs also reduce the risk of impaired growth ( 34 ) and development ( 35 ), as well as mortality ( 36 ). Neither MNPs nor SQ-LNSs were developed to replace a varied age-appropriate diet for young children, but each plays a role in improving diets that may be inadequate in some essential nutrients.…”
Section: Evidence-based Solutions Availablementioning
confidence: 99%